Pacemaker Implantation in Juvenile Neuronal Ceroid Lipofuscinosis (CLN3)–A Long-Term Follow-Up Study - Handrup, Mette Møller; Mølgaard, Henning; Andersen, Brian N.; Ostergaard, John R. (Frontiers in Neurology, 2022)
It is well documented that deteriorating heart function due to deposition of ceroid lipopigment is a significant co-morbidity in Juvenile Neuronal Ceroid Lipofuscinosis (CLN3 disease) although the exact disease mechanisms remain unknown in any NCL form. An increasing frequency of cardiac conduction disorders including severe bradycardia and sinus arrest is seen in the late teens, as is a left ventricular hypertrophy in the early 20s. Only a few case reports of pacemaker implantation have been published, and so far, no long-term follow-up study exists. As new treatment options emerge, more patients will live longer and the need for pacemaker will likely increase, why knowledge of long-term outcome is needed. In the present study, we present the course of six patients from the original Danish CLN3-heart population study (n = 29) published in 2011 in whom pacemaker implantation was indicated from a cardiac point of view. In two cases, the families deselected pacemaker implantation. In four males, aged 19-29 years, all having a good general condition, a dual-chamber pacemaker (St. Jude Medical™ Accent/Assurity MRI™) was implanted in general anesthesia without any complications. At follow-up 9 years later, three were still alive. According to the parents' opinion they still have a good quality of life, now 26, 30, and 36 years old. Pacemaker treatment is safe and may have great impact on quality of life. However, the medical indication for pacemaker treatment is relative and it is important that various aspects, including the patient's general condition and family preferences, are thoroughly discussed before making the final decision.